(untitled) (Research, Society and Development, 2021)
Objective: to evaluate the indicators of pleasure and psychic suffering experienced by cancer nursing workers in a public hospital in Rio de Janeiro. Methodology: prospective and quantitative study, being carried out in three hospital units of a public hospital specializing in oncology. Data collection occurred through the application of four pleasure and suffering scales, which make up the inventory on work and risk of illness, for 125 health workers, including nurses, technicians and nursing assistants. Results: Most participants were women, aged less than 40 years, university graduated and with more than 15 years of professional experience. The evaluation of the work context showed that 94.4% of the participants have a moderate or negative view of socio-professional relationships and working conditions. Factors related to physical, cognitive and affective cost in the work environment were rated as moderate or severe by 95.2% of the participants. Although 96% of the participants have a moderate or positive evaluation of their experiences in the work environment, most of them reported suffering from physical, psychological and social wear. Conclusion: Hospital management must promote actions considering the vision of oncology nursing workers to help cope with suffering in hospital practice, promoting the health and productivity of the entire team.